Penerapan Latihan Sepeda Statis Intradialitik dalam Memperbaiki Gejala Kelelahan pada Pasien Hemodialisis - Ernawati, Dedeh; Irawati, Diana; Anggraeni, Dewi; Jumaiyah, Wati; Abriyanti, Rika Mustika (Journal of Telenursing (JOTING), 2024)
This study aims to implement an intradialytic stationary bicycle exercise intervention to improve fatigue symptoms in hemodialysis patients. The research method used is a literature review. Research results The research results showed that there were significant differences between the experimental group and the control group on fatigue subscales such as decreased motivation (P = 0.02) and mental fatigue (P = 0.046). Also, there were significant differences between the experimental and control groups in all fatigue subscales during the third month of intervention and 1 month after intervention. In addition, the results showed that exercise prevented the development of mental fatigue in the experimental group. In conclusion, exercise with a stationary bicycle prevented an increase in fatigue and its subscales, especially mental fatigue, in the test group. Keywords: Hemodialysis, Fatigue, Stationary Bike